Qualidade do ar em instalações avícolas - Campos, Juliana Nogueira (Universidade Federal do Tocantins, 2023)
The objective of this literature review was to address air quality inside broiler facilities, equipped with ventilation systems, based on thermal comfort, animal welfare, air quality and animal performance. When considering the breeding environment, a direct correlation with environmental variables such as temperature and relative humidity is common, these factors are extremely important, having a considerable impact on the productivity of animals and the well-being of workers. But there are other factors, as they are more difficult to identify and often do not receive the attention they deserve from producers, but they are just as important. Among these factors, the levels of gases and dust present inside the facilities are particularly prominent, this can be evaluated from different perspectives, including the quality of the available air and the evaluation of its pollutants that can be inhaled, based on the existing thermodynamics. between birds and their surrounding environment and, ultimately, the risk to human health. Animal welfare is closely related to the need for comfortable conditions in which animals can perform their physical and behavioral functions, free from any stress caused by certain injuries.